2012
DOI: 10.1162/jocn_a_00100
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Extraction of Gist—Early Neural Correlates of High-level Visual Processing

Abstract: Abstract■ The human cognitive system is highly efficient in extracting information from our visual environment. This efficiency is based on acquired knowledge that guides our attention toward relevant events and promotes the recognition of individual objects as they appear in visual scenes. The experience-based representation of such knowledge contains not only information about the individual objects but also about relations between them, such as the typical context in which individual objects co-occur. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…We conclude that our analysis was successful in predicting post-experimental time reference ratings from brain activity recorded during passive stimulus viewing, providing evidence that this specific stimulus dimension might be processed automatically, without deliberately directing attention. These findings are in line with reports that the ‘gist’ or general meaning of a scene can be extracted rapidly, as early as 70 ms after exposure to a stimulus [59] , [60] . Moreover, we could predict directly from brain activity the extent to which individuals experienced some very abstract attributes of the stimuli that were not part of the explicitly depicted elements of the image (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…We conclude that our analysis was successful in predicting post-experimental time reference ratings from brain activity recorded during passive stimulus viewing, providing evidence that this specific stimulus dimension might be processed automatically, without deliberately directing attention. These findings are in line with reports that the ‘gist’ or general meaning of a scene can be extracted rapidly, as early as 70 ms after exposure to a stimulus [59] , [60] . Moreover, we could predict directly from brain activity the extent to which individuals experienced some very abstract attributes of the stimuli that were not part of the explicitly depicted elements of the image (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Ample evidence from the visual perception literature has documented the importance of semantic and spatial object-to-object relations to online unitization or to ''perceptual grouping'' processes (e.g., Auckland, Cave, & Donnelly, 2007;Davenport, 2007;Green & Hummel, 2006;Gronau & Shachar, 2014;Oppermann, Hassler, Jescheniak, & Gruber, 2012;Roberts & Humphreys, 2011). More relevant to the present research, several studies have demonstrated the significance of such unitization processes for visual memory encoding and retrieval processes (e.g., Hollingworth, 2006;Mandler & Parker, 1976;Mandler & Ritchey, 1977).…”
Section: Discussionmentioning
confidence: 64%
“…We demonstrated the feasibility of a role for SSVEPs in unraveling the contribution of simultaneous neuronal processes involved in the perception of scenes. Future studies should combine experimental designs that allow the analysis of SSVEPs and of markers of ultrafast categorization processes (Müller and Hillyard, 2000;Oppermann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%